La devolución del impuesto al valor agregado y su incidencia en la liquidez en las empresas PYMES productoras de camarón domiciliadas en la ciudad de Guayaquil, periodo 2014-2015 - Ventura Chavarría, Olga Patricia (2019)
The shrimp sector is one of the most important in Ecuador due to the high generation of foreign currency in the country with a dollarized economy, in many cases this type of companies is affected by the lack of liquidity due to the liabilities they have, the government encourages them through the VAT refund of the purchases that are used in the elaboration of the finished product, so that they increase their liquidity and can cover the obligations that the company has. In the present investigation, the descriptive, correlational and field methodology was applied since information was collected on VAT refund procedures with a mixed approach: quantitative and qualitative using techniques such as the survey, the interview and data analysis with secondary information. provided by a database of the Internal Revenue Service (SRI), achieving compliance with the objectives set……….